The influence of cognitive satisfaction on the relationship between salesperson presentation skills and customer's intention to repurchase - Wan Omar, Maznah; Ismail, Ishak; Abd Wahid, Nabsiah (2007)
The application of sales presentation skills by the sales force during their interaction with customers in the sales situation can have a significant effect on customer intention to repurchase in the Malaysian Computer retail business. The purpose of this paper is to examine the relations between important sales presentation skills and the relative roles played by cognition in the development of customer satisfaction which will lead to customer’s intention to repurchase in a computer retail setting in Malaysia. This will then lead to increased benefits for the organization in the form of customer loyalty. The cognitive evaluation of customer satisfaction was found to explain customer’s intention to repurchase in a retail setting in the Malaysian market. This finding holds importance to those retailers who have been able to generate high expectations in the eyes of their customers.